The application of 28-homocatasterone brassinosteroid reduces blossom end rot in ‘BRS Montese’ tomatoes (Revista de Ciências Agroveterinárias, 2022)
We assessed the effect of 28-homocatasterone on xylem functionality and its relationship with blossom end rot (BER) occurrence and the quality of 'BRS Montese' tomatoes. Tomato plants were cultivated in a protected environment, with a semi-hydroponic system. During full flowering, open flowers were selected, marked, and pollinated. After two days, the flowers received the application of 28-homocatasterone at a concentration of 10-6 M or deionized water (control). Treatments were reapplied weekly up to 24 days after the first application (DAFA). At 24 DAFA, fruits were harvested and evaluated for fresh mass, texture (skin rupture and pulp penetration forces), skin color, xylem functionality, membrane permeability, apoplastic calcium concentration, and BER incidence. The application of 28-homocatasterone at 10-6 M did not increase the fresh mass nor change the fruits' texture attributes. However, 28-homocatasterone increased or kept xylem functionality, which was assicated with increased apoplastic calcium concentration and reduced BER occurrence in 'BRS Montese' tomatoes. Thus, the application of 10-6 M catasterone could be an alternative for BER control in tomatoes.
Keywords: Solanum lycopersicum; calcium; physiological disorder; Lycopersicon esculentum; xylem